Comparison Between Two NSAIDs (Non selective & selective COX-2 Inhibitor) According to their Renal Toxicity on Elderly People - Haydar F. Hadi (Al-Mustansiriyah Journal of Pharmaceutical Sciences, 2007)
The nonsteroidal anti-inflammatory drugs (NSAIDs) are widly used all over the world for different rheumatic musculoskeletal disorders. Like any other chemical compounds, they have different side effects like renal toxicity that becomes very serious when used for long time especially from elderly people whose already have a reduced renal function or those This with renal or cardiac problems that may increase the incidence of such toxicity.